2018
DOI: 10.1055/s-0043-123645
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Track to Hypoalgesia – The Anaerobic Exercise Effect on Pain Sensitivity

Abstract: Maximal anaerobic exercise, is a short high intensity effort, involves activation of the hypothalamus-pituitary-adrenal axis, and may suggest hypoalgesic effects. In addition, this exercise-induced muscle pain may contribute to hypoalgesia via the pain inhibits pain phenomenon, which is related to the diffuse noxious inhibitory control (DNIC) mechanism. We aimed to investigate whether: 1) a single bout of 30 s maximal anaerobic exercise has an analgesic effect on experimental pain sensitivity; 2) DNIC is the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
1
12
0
1
Order By: Relevance
“… 195 Findings on the influence of aerobic exercise duration are more equivocal, with one study observing a dose-response with larger effects after bicycling for 30 minutes compared with 10 minutes, 69 and one study observing no difference between bicycling for 10 minutes compared with 20 minutes. 195 Moreover, the fact that very short-duration aerobic exercise can elicit EIH 129 , 162 implies that intensity, or the combination of intensity and duration, may be more important for determining the size of EIH after aerobic exercise than either variable alone.…”
Section: Pain Outcomes After Acute and Regular Exercise In Pain-frmentioning
confidence: 99%
See 2 more Smart Citations
“… 195 Findings on the influence of aerobic exercise duration are more equivocal, with one study observing a dose-response with larger effects after bicycling for 30 minutes compared with 10 minutes, 69 and one study observing no difference between bicycling for 10 minutes compared with 20 minutes. 195 Moreover, the fact that very short-duration aerobic exercise can elicit EIH 129 , 162 implies that intensity, or the combination of intensity and duration, may be more important for determining the size of EIH after aerobic exercise than either variable alone.…”
Section: Pain Outcomes After Acute and Regular Exercise In Pain-frmentioning
confidence: 99%
“… 130 Controlled studies using similar methodology but different designs (eg, crossover trials and parallel trials) have also been conducted. 80 , 162 , 195 , 204 The results of these studies, especially those where participants were randomized to exercise or control, or where the order of exercise and control were randomized and counterbalanced for crossover trials, give a less biased estimate of the effect of a single bout of exercise on pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain causes an increase in HR and BP by activating the sympathetic nervous system (31). Recent research indicates that acute anaerobic exercise can mitigate the sensation of pain (32), possibly decreasing the cold pressor test-mediated cardiovascular response following exercise. In the present study, the participants reported a significantly greater decrease in pain sensation after the ECT compared to ET.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike PPT, this parameter involves inputting repetitive noxious stimuli at a constant intensity and measuring the level of pain facilitation through these stimuli. Improvement, that is, decrease in TS, is considered an important marker of central nervous system sensitization in patients with CNSLBP (Arribas‐Romano et al, 2020; Corrêa et al, 2015; Leite et al, 2018; Samuelly‐Leichtag et al, 2018). On the other hand, CPM is a psychophysical measure measured in humans and is correlated with the diffuse noxious inhibitory control (DNIC) mechanism (Lima et al, 2017), initially identified in rats and suggested as a phenomenon in which ‘pain inhibits pain’.…”
Section: Discussionmentioning
confidence: 99%